Pengaruh Green Product dan Brand Image terhadap Customer Loyalty Melalui Customer Satisfaction Sebagai Variabel Intervening: Studi pada Konsumen Produk Oriflame di Surabaya - Dhiya’ Ayu Adibah; Budi Prabowo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine and analyze the influence of green products on customer satisfaction, the influence of brand image on customer satisfaction, the influence of green products on customer loyalty, the influence of brand image on customer loyalty, the influence of customer satisfaction on customer loyalty, the influence of green products on customer loyalty through customers. Satisfaction and the Influence of Brand Image on Customer Loyalty Through Customer Satisfaction among Oriflame Product Consumers in Surabaya. The population in this research is Oriflame Product Consumers in Surabaya. The sample used was 100 taken using purposive sampling technique. Data analysis in this research used SEM-PLS with SmartPLS software version 4.0. The research results show that Green Product (X1) has a significant effect on Customer Satisfaction (Z). Brand Image (X2) has a significant effect on Customer Satisfaction (Z). Green Product (X1) has no significant effect on Customer Loyalty (Y). Brand Image (X2) has a significant effect on Customer Loyalty (Y). Customer Satisfaction (Z) has a significant effect on Customer Loyalty (Y). Green Product (X1) has a significant effect on Customer Loyalty (Y) through Customer Satisfaction (Z). Brand Image (X2) has a significant effect on Customer Loyalty (Y) through Customer Satisfaction (Z).